TANTANGAN DAN PELUANG IMPLEMENTASI KEBIJAKAN ZERO WASTE DI KOTA BAUBAU - Farid Yusuf Nur Achmad (Journal Publicuho, 2024)
This research aims to evaluate implementing the Zero Waste policy in Baubau City, focusing on identifying challenges and opportunities encountered in the implementation process. The research method used is qualitative, with data collection conducted through in-depth interviews and direct observation in the field. The results of the study indicate that despite efforts from the government to promote the concept of Zero Waste and improve waste management infrastructure, several challenges still hinder the implementation of the policy. The main challenges identified include the lack of public awareness about the importance of sustainable waste management, limitations in waste management infrastructure, and the lack of active participation from the community in Zero Waste programs. However, the research also reveals significant opportunities to enhance the implementation of Zero Waste policy through collaboration with the private sector and NGOs, as well as through participatory approaches and community empowerment. By strengthening collective commitment and active participation from all stakeholders, it is hoped that Baubau City can successfully achieve the Zero Waste goal and serve as an example of environmentally friendly and sustainable waste management.